Razão e emancipação: uma leitura a partir de Theodor W. Adorno - Bido, José Mateus (2012)
The dissertation seeks to establish the relationship between reason and emancipation from the reading of Theodor W. Adorno. This dialogue is based on the view that rationality carries with it the potential to overcome the project reifies imposed by consumer society. The capability is critical rationality credit to the constitution of an individual's training process for its rational and political emancipation. Emancipation rational causes the individual to become conscious of itself as being contingent and historical, as distinct from another, but that requires the other to form the non-identical. Political emancipation causes the individual to connect with people and institutions, such that its action is measured not by the autonomy and heteronomy. Thought and action are worked by Adorno as two intrinsic conditions of the same process that permeate and establishing the realities, problems. Are characteristic elements themselves and the human condition in history and are to give people the knowledge and eliminate / overcome the bonds establishing the identity mass. Thought and action are epistemologically placed to lead the contemporary society, a dialectical process, for continuing training, so that the atrocities are identified, reported and avoided. A reflection and action, with features behave as constant criticism of themselves, potentiate the opening for the new, resisting the given position dialectically in a process of emancipation. Thought, therefore, from the historical context, the concept of emancipation, it is therefore more than a situational condition that involves the individual in intellectual clarity for decision making, free-form. Adorno's conception of emancipation becomes a project that a free and democratic society must pursue and enable its members, giving the conditions for achieving an identity through a cultural constant. The condition of an enlightened individual with a view to Adorno, is implicitly linked to the process of its formation, by a broad education. Education leads to a different conception of reason: historical reason not absolute reason (perenis). This condition presents itself as a training opportunity that can lead to intellectual maturity, human and cultural order that the individual understands the difference in meaning between autonomy and act for act on heteronomy. The difference between acting and acting autonomously motivated by heteronomous motivation. The difference between acting on their own initiative and act by force or external initiative. The understanding of emancipation is now seen as a project and training processes, both taken from the perspective of the notion of a liberating rationality, front reifying the scope of the consumer society.